Tema-rema struktur og oversættelse - Anna-Lise Laursen (Hermes, 1989)
This paper demonstrates how the Prague School theories of Functional Sentence Perspective (FSP) and Thematic Progression can be used to enlighten certain text-relevant aspects of the translation of the sentence. A model is presented which includes a solution to the FSP-related problem of language-specific grammatical word-order rules by means of a mix of parameters that takes care of the bipartition of the sentence into a thematic and a rhematic section. On the basis of the results of a previously conducted contrastive analysis of a corpus of Spanish and Danish newspaper articles, in which the thematic sections have been studied, it is argued that the divergent tendencies in the two corpora as to the realization of the thematic elements and the thematic progression can motivate certain adaptations of the thematic section in the translation process.